The large city : a world problem - Hicks, Ursula Kathleen (New York : Wiley, 1974)
This book aimed at discussing the characteristics troubles of large cities in sufficient detail to form a basis for a judgement of the nature and seriousness of their trouble.
"A Halsted Press book."
Includes bibliographical references.
ijb, 17/01/2019
Loans
Keywords: Cities and towns; Underdeveloped areas - Cities and towns; Cities and towns - Japan; Japan